Risk Factors for Ischemic Heart Disease in an Urban Area of Japan: A Case-Control Study in AMHTS - Kashihara, H.; Ohno, H.; Tamura, M.; Kawakubo, K.; Gunji, A. (Methods of Information in Medicine, 2000)
Objectives: In Japan controversy exists as to whether or not the risk factors for ischemic heart disease (IHD) are the same as in western countries. We conducted a case-control study on IHD to clarify the risk factors in males in an urban area of Japan using our automated multiphasic health testing and services (AMHTS) system. Method: Cases were the clients who took the health check-up between January 1987 and July 1994 and had onset of IHD after the check-up. For each case five clients were selected as controls by conditional matching. The check-up data were compared between cases and controls 11 years, 6 years and just before the onset of the heart diseases. Results: The statistically significant items were as follows: (1) Eleven years before the onset: Total cholesterol (T-Chol) for myocardial infarction (MI), and fasting blood sugar (FBS) for angina pectoris (AP). (2) Six years before the onset: T-Chol, electrocardiographic (ECG) findings and the complaint of palpitation or breathlessness for MI, and FBS and palpitation or breathlessness for AP. (3) Just before the onset: T-Chol, the complaint of chest pain, FBS, smoking index and hypertensive status for MI and palpitation or breathlessness, ECG findings, chest pain, systolic blood pressure and erythrocyte sedimentation rate at 60 minutes for AP. In conclusion, the risk factors for MI in males in an urban area of Japan are the same as in western countries. The most significant risk factor for AP in males in an urban area of Japan is fasting blood sugar.
Keywords: Ischemic Heart Disease; Risk Factors